Top 10 public health challenges to track in 2023: Shifting focus beyond a global pandemic - Don Eliseo Lucero‐Prisno III; Deborah Oluwaseun Shomuyiwa; M. B. N. Kouwenhoven; Thinley Dorji; Goodness Ogeyi Odey; Adriana Viola Miranda; Isaac Olushola Ogunkola; Yusuff Adebayo Adebisi; Junjie Huang; Lin Xu; Joseph Christian Obnial; Aminath Huda; et al. (Wiley, 2023)
Abstract The year 2022 saw COVID‐19 as the primary public health concern, with vaccine rollout and mandates at the forefront. Other viral infectious diseases, such as Monkeypox and Ebola, emerged as public health concerns. Climate change and political conflicts significantly impacted global health, increasing the demand for humanitarian assistance and protection. In 2023, it remains crucial to identify global and public health priority areas to coordinate and implement effective solutions. Through discussions with public health practitioners and researchers, we have identified key priority areas for 2023, namely, health systems, the mental health crisis, substance abuse, infectious diseases, malnutrition and food insecurity, sexual and reproductive health challenges, environmental pollution, the climate crisis, cancer, and diabetes. These priority areas highlight shared concerns that should be addressed to facilitate proactive and innovative health interventions and practices. To achieve universal healthcare targets for 2030, prioritization, financial investment, international cooperation, and collaboration in addressing these global health challenges are crucial. This requires coordination among public health decision‐makers, the private health sector, and opinion leaders to implement country‐specific healthcare financing and food security measures. Research, scientific knowledge, and technical capacities must be leveraged to produce sustainable interventions that effectively reduce health disparities and improve health system responsiveness to prevent these challenges from progressing to public health emergencies.